Differential Protein Expression in Small Intestinal Neuroendocrine Tumors and Liver Metastases - Kim, Michelle Kang (Pancreas, 2016)
OBJECTIVES: Small intestinal neuroendocrine tumors (SI-NETs) are often detected after they have become metastatic. Using a novel protein array, we identified pathways important in SI-NET metastasis development in surgically resected patients. METHODS: Paired primary tumors and liver metastases from 25 patients undergoing surgical resection for metastatic SI-NETs were harvested. Extracted proteins were separated by SDS gel, and multiplex immunoblots were performed with 136 antibodies. Significant Analysis of Microarray was used to select for differentially expressed proteins. A tissue microarray was constructed from 27 archived specimens and stained by immunohistochemistry. RESULTS: Comparing primary SI-NETs to matched normal small bowel mucosa, 9 proteins were upregulated and Cyclin E was down-regulated. SI-NET liver metastases demonstrated up-regulation of P-ERK and p27 but down-regulation of CDK2 and CDC25B. When comparing primary SI-NET with their paired liver metastases, cyclin E demonstrated a significant up-regulation in the liver metastasis. Tissue microarray demonstrated higher p38 expression and lower Cdc 25b expression in SI-NETs vs liver metastases and confirmed higher expression of p27 in liver metastases vs normal liver. CONCLUSIONS: Few studies have compared protein expression in paired primary and metastatic SI-NETs. Our findings reveal changes in a limited number of proteins, suggesting these may be targets for therapy.